2011
DOI: 10.1155/2011/575476
|View full text |Cite
|
Sign up to set email alerts
|

Province‐wide Adenovirus Type 3 Outbreak with Severe Cases in New Brunswick

Abstract: Adenovirus is a commonly isolated virus in clinical samples. Life-threatening infections, although rare, are described worldwide. An epidemic spread of an adenovirus type 3 strain occurred in the province of New Brunswick during the fall of 2008 to the winter of 2009; it resulted in three severely ill patients, with one fatality. Adenovirus should be considered as a cause of severe community-acquired viral pneumonia, especially when the influenza test is negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A survey from the from the World Health Organization (WHO) reveals that HAdV-3 was responsible for 13% of all adenoviral infections from 1967 to 1976 [ 3 ]. Over the last few years of HAdV-3 has become the major agent of acute respiratory infection worldwide and encompassing 15 to 87% of adenoviral respiratory infections [ 2 , 4 6 , 12 , 13 , 16 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…A survey from the from the World Health Organization (WHO) reveals that HAdV-3 was responsible for 13% of all adenoviral infections from 1967 to 1976 [ 3 ]. Over the last few years of HAdV-3 has become the major agent of acute respiratory infection worldwide and encompassing 15 to 87% of adenoviral respiratory infections [ 2 , 4 6 , 12 , 13 , 16 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because clinicians do not always perform diagnostic tests for respiratory illnesses, cases of HAdV-14 infection might be diagnosed simply as acute respiratory illnesses or as unspecified sporadic viral pneumonias. During a 2008–2009 outbreak of adenovirus type 3 in New Brunswick, the same province in which the current study patient lived, we serotyped 17 strains and found no evidence of HAdV-14 ( 10 ). Moreover, a large 2007 Canadian study in the Toronto region failed to find any HAdV-14 strains among the 200 strains that were submitted; circulating HAdV strains were largely subtypes 1, 2, and 3 ( 11 ).…”
Section: Discussionmentioning
confidence: 72%
“…HAdV is one of the major causative pathogens of severe acute respiratory disease in human beings. Although most of respiratory infections caused by HAdVs are self-limiting, fatal infections also occur in children and adults [ 19 , 25 27 ]. In this retrospective study, HAdV was the third most frequent pathogen which causes 12% children hospitalized due to ARI (495/4,130).…”
Section: Discussionmentioning
confidence: 99%